Interfacing Research and Policy in Informing Data Management for Quality Data in Health Information Systems: Case of DHIS2in Malawi. (Journal of Health Informatics in Africa, 2021)
AbstractLike in many other fields, there is an ever growing need for new knowledge in health services delivery on how we should better our decisions in delivering our services. In response to that desire of knowledge Universities and other institutions have been funding and motivating students and academicians into research. The expectation is that knowledge acquired from research will inform us how to improve our practices.MethodThis qualitative desk research attempted to answer the question how research, policy and practice in health information system interface each other to inform design and implementation of health information systems. It used DHIS2 in Malawi as a case, PhD and masters students’ theses, Health Information System Policy and Strategy to explore how these resources inform each other. Data analysis was done through thematic tabular analysis, and themes were derived from predefined set of criteria.ResultsThe findings showed that there is considerable effort by researchers to publish and share their findings to practitioners through conference, journals and working together in workshops. It also shows that participation in policy formulation workshop has been a key means by which researchers directly contribute to practitioners works.ConclusionThere is considerable effort by stakeholders to create and make use of platforms that should enable the link between researchers and practitioners. The paper has to a considerable extent, managed to answer how research, policy and practice in health information system interface each other to inform design and implementation of health information systems. Apart from that it has most importantly, stimulated a need to conduct a detailed field study to ascertain how actually the researchers work inform practitioners on the ground.